1997
DOI: 10.1093/ageing/26.suppl_2.43
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Restraint Use in Nursing Homes in Eight Countries

Abstract: Background: the use of restraints in nursing homes varies among countries and institutions. However, in many countries, no reliable data exist, although restraints use is acknowledged. Method: we compare data of the type of restraints used (trunk, limb or chair that prevents rising) and the intensity of its use in eight countries: Denmark, France, Iceland, Italy, Japan, Spain, Sweden and the USA. We report these data in total and for groups of residents with similar functional abilities and cognitive performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 16 publications
5
41
0
1
Order By: Relevance
“…Restraint use may be much higher at night when staffing levels are lower. Physical restraint use is substantially lower among nursing homes in many other developed countries, ranging from 2 to 9% of facility residents (Ljunggren, Phillips, & Sgadari, 1997). This, and the fact that restraint use rates in U.S. nursing homes vary widely, suggests that many facilities here could function with lower rates of use than are currently employed.…”
Section: Introductionmentioning
confidence: 99%
“…Restraint use may be much higher at night when staffing levels are lower. Physical restraint use is substantially lower among nursing homes in many other developed countries, ranging from 2 to 9% of facility residents (Ljunggren, Phillips, & Sgadari, 1997). This, and the fact that restraint use rates in U.S. nursing homes vary widely, suggests that many facilities here could function with lower rates of use than are currently employed.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these a strict definition has been applied (Capezuti et al, 1996;Fletcher, 1996;Karlsson et al, 1996;Ljunggren et al, 1997;Castle and Mor, 1998;Retsas, 1998;Sullivan-Marx et al, 1999;Castle, 2000), limiting the studies to actions like the restriction of movement or normal access to the body, or to the use of mechanical devices. A few studies include chemical restraints (Fletcher, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A Dutch study on cognitively impaired residents found 32% were regularly restrained (Hamers et al, 2004). Ljunggren found prevalence as high as 40% across several nations (Ljunggren et al, 1997).…”
Section: Discussionmentioning
confidence: 99%